The Interactions of the Marketing Mix, Entrepreneurial Behavior, and Product Innovation on the Income of Micro, Small, and Medium Enterprises - Ratang, Westim; Marlissa, Elsyan R. (AIBPM Publisher, 2023)
The primary objective of this study is to investigate the interplay between the marketing mix, entrepreneurial behavior, and product innovation in relation to the financial performance of micro, small, and medium firms located in Jayapura. A quantitative experimental research methodology was employed to conduct a study on micro, small, and medium enterprises in Jayapura. The survey included a total of 129 respondents. Following reliability, validity, and classic assumption tests, hypothesis developments were tested using the Structural Equation Model. The results of this study found significant interactions between entrepreneurial behavior and product innovation and between marketing mix and product innovation. The results also found significant effects of entrepreneurial behavior, marketing mix, and product innovation on business income. This study provides empirical evidence that better entrepreneurial behavior and implementation of a marketing mix will increase product innovation in Jayapura. This study also suggests that better entrepreneurial behavior, better implementation of the marketing mix, and better product innovation will increase the business income of micro, small, and medium entrepreneurs in Jayapura.